2021
DOI: 10.1039/d0qo01299h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in visible-light photocatalytic deuteration reactions

Abstract: Deuterated organic compounds have widespread applications in many fields such as medicinal chemistry, mechanistic studies, and quantitative analyses. Traditionally, the incorporation of deuterium atom into organic compounds can be achieved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 120 publications
0
44
0
3
Order By: Relevance
“…A rapidly growing number of chemical transformations employs DPZs as photocatalysts [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. In 2020, Jiang et al reported a radical-based asymmetric olefin difunctionalization strategy for rapidly forging all-carbon quaternary stereocenters α to diverse azaarenes (Scheme 4) [64].…”
Section: Applications In Photoredox Chemistrymentioning
confidence: 99%
“…A rapidly growing number of chemical transformations employs DPZs as photocatalysts [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. In 2020, Jiang et al reported a radical-based asymmetric olefin difunctionalization strategy for rapidly forging all-carbon quaternary stereocenters α to diverse azaarenes (Scheme 4) [64].…”
Section: Applications In Photoredox Chemistrymentioning
confidence: 99%
“…Accordingly, significant advances have been made in the deuteration/tritiation of organic compounds via metal-and photocatalysis. [45][46][47][48][49][50][51][52][53] A notable example is the deuteration and tritiation of aromatic C(sp 2 )-H bond using a homogeneous iron catalyst, reported by the Chirik group. 48 This method shows an orthogonal selectivity to the traditional ortho-directing Crabtree iridium catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In this context, the emergence of photocatalysis has provided enormous opportunities for C-H functionalization through direct photo hydrogen atom transfer (HAT) catalysis or by the synergistic combinations of photoredox with HAT catalysis. [9][10][11][12][13][14][15][16][17][18] Aldehydes, one of the most abundant and readily available feedstocks, are enabled to generate acyl radicals to achieve umpolung reactivity by photo-induced HAT in a step-and atom-economic fashion. [19][20] However, the acceptors of acyl radicals were limited to electron-de cient alkenes and radical trappers containing electron-withdrawing leaving groups, [21][22][23][24][25] to result in an electrophilic radical intermediate to turn over the redox-neutral photocatalytic cycle ( Fig.…”
Section: Introductionmentioning
confidence: 99%